AGROFORESTRY DESIGN ON COMMUNITY FOREST LAND TO IMPROVE THE QUALITY OF ECOSYSTEM SERVICES OF CARBON SEQUESTRATION AND STORAGE AND HYDROLOGY IN WANGUNJAYA VILLAGE, CUGENANG DISTRICT, CIANJUR REGENCY, WEST JAVA - Diwanty Tasyabita, Najwa
Community forest development is an alternative solution to reduce land-use change issues and can improve the welfare of communities around forest areas. In community forests in Cianjur Regency, people plant bamboo alongside local trees, especially those that are the main commodities in the community forests. In selecting the types of plants to be planted, the community chooses economically valuable species for the community forests. However, various studies suggest that considering ecological aspects is also important, as it will affect the suitability and sustainability of the selected species. Bamboo is a grass plant from the Poaceae family that is widely found and utilized by the community in Cianjur Regency. This study aims to analyze the distribution pattern and interspecific association of bamboo with local trees in 10 sub-districts of Cianjur Regency by calculating the Importance Value Index (IVI), Morisita's Index of Dispersion, and Jaccard Association Index. The method includes measuring environmental factors such as temperature and air humidity, which show relatively similar values, and vegetation analysis using the quadrat method, with plot determination by purposive sampling within a 0.1-hectare plot. The average temperature and air humidity measurements at the study location are 32.7°C and 43.2%, respectively. Other research results show that 1) the IVI at the tree level is dominated by Gigantochloa apus (67.09%) and Tectona grandis (58.66%), while at the pole level, it is dominated by Falcataria moluccana (142.77%) and Tectona grandis (38.65%); 2) the clumped distribution pattern is found in species Gigantochloa apus, Tectona grandis, Falcataria moluccana, Gnetum gnemon, Durio zibethinus, and Bambusa vulgaris, while Sandoricum koetjape and Gigantochloa pseudoarundinacea are found with a random distribution pattern; 3) Gigantochloa apus with Falcataria moluccana and Tectona grandis with Falcataria moluccana are positively associated with association index values of 0.227 and 0.037, respectively; while Falcataria moluccana with Hibiscus macrophyllus is negatively associated with a value of 0.263. All association index values are considered low.